Does structural parasitism by epiphytes exist? A case study between Tillandsia recurvata and Parkinsonia praecox. (2nd November 2015) - Flores‐Palacios, A.
Abstract: The effects that epiphytes have on their hosts have been poorly explored in an experimentally. Correlational evidence suggests that epiphytes may be either mutualists or structural parasites, as has been proposed for Tillandsia recurvata on Parkinsonia praecox . To test the effect of T. recurvata upon P. praecox, the epiphyte load on branches of P. praecox was measured and two 1‐year experiments were performed to detect the effect of transplantation/removal of epiphytes and shade (0%, 35%. 50% and 80%) on shoot dynamics. If T. recurvata represents a selective pressure for P. praecox, then the frequency of branches carrying large epiphyte loads will be high, and host shoot survival will decrease in the presence of T. recurvata and with increased shade. A weak inverse relationship between epiphyte load and percentage of dead shoots in the host was detected. Shoot survival was independent of epiphyte presence. Shade decreased shoot survival by 35–72%. Results suggest that at the study site, T. recurvata is a commensalist of P. praecox . An alternative hypothesis to explain the correlation between high epiphyte load and branch/tree decay is that older branches carry more epiphytes, receive more shade from neighbouring branches and could be undergoing a natural decline process.